Genetic identity of Malnad gidda, Puganur and Vechur – Indian breeds of dwarf cattle - DAS, D N; RAO, M K; REDDY, A OBI; MURTHY, L K (The Indian Journal of Animal Sciences, 2012)
Malnad gidda, Punganur and Vechur, native breeds of Karnataka, Andhra Pradesh and Kerala, respectively, are small in size with low productivity profile. These dwarf cattle do not require any special management care in terms of feeding, herd management and health care. In addition to this, these breeds are known for disease resistance and adaptability to the hot, humid and high rainfall areas with low input situations. The results, in terms of inter-breed similarity indices, MAPD and genetic distance estimates, revealed that there are some differences among these dwarf breeds. However, low estimates of both MAPD as well as genetic distance indicated that these dwarf cattle breeds might have originated from a common source in the distant past. Probably due to the process of evolution and through implication of natural selection after migration from a common source and remained confined to a particular geoclimatic region for years together, the major genes controlling qualitative characters might have been fixed in these dwarf breeds thereby creating some inter-breed differences.